Prognostic value of neutrophil-to-lymphocyte ratio in locally advanced non-small cell lung cancer treated with concurrent chemoradiotherapy - Park, Eun Young (Radiat Oncol J, 2019)
PURPOSE: This study aimed to investigate neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic factors in patients with locally advanced non-small cell lung cancer (NSCLC) who received concurrent chemoradiotherapy (CCRT). MATERIALS AND METHODS: We retrospectively analyzed 66 patients with locally advanced NSCLC treated with definitive CCRT. Among these patients, 95% received paclitaxel/carboplatin or docetaxel/cisplatin. The median radiation dose was 66 Gy in 33 fractions. The NLR and PLR before/after CCRT were evaluated. The maximally selected log-rank test was used to obtain the cutoff values related to the overall survival (OS). RESULTS: Patients with high post-CCRT NLR (>3.12) showed worse OS, locoregional progression-free survival (LRPFS), and distant metastasis-free survival (DMFS) than those with low NLR (2-year OS: 25.8% vs. 68.2%, p < 0.001; 2-year LRPFS: 12.9% vs. 33.8%, p = 0.010; 2-year DMFS: 22.6% vs. 38.2%, p = 0.030). Patients with high post-CCRT PLR (>141) showed worse OS and LRPFS than those with low PLR (2-year OS: 37.5% vs. 71.1%, p = 0.004; 2-year LRPFS: 16.5% vs. 40.3%, p = 0.040). Patients with high NLR change (>1.61) showed worse OS and LRPFS than those with low NLR change (2-year OS: 26.0% vs. 59.0%, p < 0.001; 2-year LRPFS: 6.8% vs. 31.8%, p = 0.004). The planning target volume (hazard ration [HR] = 2.05, p = 0.028) and NLR change (HR = 3.17, p = 0.025) were the significant factors for OS in the multivariate analysis. CONCLUSION: NLR change after CCRT was associated with poor prognosis of survival in patients with locally advanced NSCLC. An elevated NLR after CCRT might be an indicator of an increased treatment failure risk.